2016
DOI: 10.1111/1346-8138.13661
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adalimumab treatment on cardiovascular risk biomarkers in psoriasis: Results of a pilot study

Abstract: Psoriasis is a chronic systemic immune-mediated inflammatory dermatosis associated with several comorbidities. Psoriasis patients are at increased risk of developing cardiovascular diseases (CVD), namely, coronary heart disease, stroke or peripheral vascular disease, and psoriasis seems to be an independent cardiovascular risk factor. Antipsoriatic systemic therapy, especially anti-tumor necrosis factor (TNF)-a, seems to exert a beneficial effect on these comorbidities. The purpose of this study was: (i) to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 42 publications
2
27
0
1
Order By: Relevance
“…There are limited data available on the impact of systemic psoriasis treatments on metabolic and cardiovascular parameters. A study of adalimumab in 21 patients demonstrated a decrease at 12 weeks in E‐selectin and IL‐22, but no impact on vascular inflammation was seen with adalimumab in an FDG‐PET imaging study . Ixekizumab, which also targets IL‐17A, showed a neutral impact on metabolic parameters .…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data available on the impact of systemic psoriasis treatments on metabolic and cardiovascular parameters. A study of adalimumab in 21 patients demonstrated a decrease at 12 weeks in E‐selectin and IL‐22, but no impact on vascular inflammation was seen with adalimumab in an FDG‐PET imaging study . Ixekizumab, which also targets IL‐17A, showed a neutral impact on metabolic parameters .…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α inhibitors or methotrexate, decrease the risk of death due to cardiovascular incidents. Gkalpakiotis et al [49] showed a decrease in E-selectin and IL-22 concentration in serum after 3 month of therapy with adalimumab in patients with moderate to severe psoriasis. Similarly Wu et al confirmed a statistically significant reduction of CRP concentration in patients suffering from psoriasis, psoriatic arthritis, and rheumatoid arthritis after the treatment with methotrexate and TNF-α inhibitors [50].…”
Section: Sercowo-naczyniowychmentioning
confidence: 99%
“…Gkalpakiotis i wsp. [49] wykazali zmniejszenie stężenia w surowicy E-selektyny i IL-22 po 3 miesiącach terapii adalimumabem u pacjentów z łuszczycą umiarkowaną do ciężkiej. Podobnie Wu i wsp.…”
Section: Metabolic Disordersunclassified
“…The high cost of biologicals limits access to these medications; however, cost‐saving biosimilars are rapidly advancing to the market worldwide . Biologicals are effective not only for psoriasis but also for co‐morbid cardiovascular and metabolic diseases . In addition, monitoring of infection is mandatory to avoid serious consequences .…”
Section: Current Pathogenesis Of Psoriasis and Its Treatmentsmentioning
confidence: 99%
“…[89][90][91] Biologicals are effective not only for psoriasis but also for co-morbid cardiovascular and metabolic diseases. 92,93 In addition, monitoring of infection is mandatory to avoid serious consequences. [94][95][96] The emergence of antidrug antibodies is another important issue that reduces the treatment response and promotes treatment failure during biological therapy.…”
Section: Current Pathogenesis Of Psoriasis and Its Treatmentsmentioning
confidence: 99%